2010
DOI: 10.3354/ame01371
|View full text |Cite
|
Sign up to set email alerts
|

Diel variations in frequency of dividing cells and abundance of aerobic anoxygenic phototrophic bacteria in a coral reef system of the South China Sea

Abstract: With the ability of photoheterotrophic metabolism, aerobic anoxygenic phototrophic (AAP) bacteria are an important bacterial group in the marine microbial community. We investigated the diel variations of AAP bacteria in the coral reef water of the South China Sea, and report, for the first time, the frequency of dividing cells (FDC) of AAP bacteria. Our results showed that AAP bacterial abundance ranged from 1.54 × 10 4 ± 3.21 × 10 2 to 3.59 × 10 4 ± 3.04 × 10 3 cells ml -1. The diel pattern of AAP bacterial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…The most obvious is the difference in methodology. Incubations in our study were only 1 hour as opposed to the 18-72 h needed to detect the activity of AAP bacteria through the change in BChl a concentrations (Koblížek et al, 2005;Koblížek et al, 2007), whereas no incubation is needed for the frequency of dividing cell method (Hagströ m et al, 1979;Liu et al, 2010). Another methodological difference is that our approach assumes that AAP activity is adequately traced by the incorporation of 3 H-leucine.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The most obvious is the difference in methodology. Incubations in our study were only 1 hour as opposed to the 18-72 h needed to detect the activity of AAP bacteria through the change in BChl a concentrations (Koblížek et al, 2005;Koblížek et al, 2007), whereas no incubation is needed for the frequency of dividing cell method (Hagströ m et al, 1979;Liu et al, 2010). Another methodological difference is that our approach assumes that AAP activity is adequately traced by the incorporation of 3 H-leucine.…”
Section: Discussionmentioning
confidence: 98%
“…Studies using the BChl-turnover approach found that growth rates of AAP bacteria were as much as 3 per day (Koblížek et al, 2005;Koblížek et al, 2007;Hojerová et al, 2011), substantially higher than bacterial growth rates expected for these systems (Ducklow, 2000). Similarly, frequency of dividing cell data indicate that growth rates of AAP bacteria are about threefold higher than rates for other bacteria (Liu et al, 2010). In the Delaware estuary, in contrast, AAP bacteria were 40-60% more active than other bacteria in taking up leucine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AAPB are primarily heterotrophic, but they also possess the capability of harvesting light for energy and are present in all of the world's oceans (19,20). AAPB are closely associated with phytoplankton to comprise the dissolved organic carbon (DOC) in marine environments (20,48), and they grow much faster than other heterotrophic bacteria (26). Since they are 2 to 3 times larger in cell size than other heterotrophic bacteria (36), AAPB can be grazed upon more easily by predators (37), and thus they contribute a larger proportion of carbon to the upper trophic levels.…”
mentioning
confidence: 99%
“…Other studies using different approaches to calculate growth rates of AAP have reported even higher differences in their growth rate relative to total bacteria. Liu et al (2010) reported a 4-fold higher average AAP growth rate, estimated on the basis of the fre- Table 2. Summary of growth rates of total bacteria (Total) and aerobic anoxygenic photo trophic bacteria (AAP) from marine and freshwater systems and the corresponding mean relative abundance of AAP.…”
Section: Discussionmentioning
confidence: 99%